Trimming tiers - Motivations and means for de-risking select agents - Wells, Elizabeth; Grisham, Christopher; Parker, Michael T. (Frontiers in Bioengineering and Biotechnology, 2025)
In the United States, pathogens and toxins that pose a significant threat to public health are regulated via the Select Agents and Toxins list (SATL). Of those on the list, biological select agents and toxins (BSAT) deemed especially dangerous are designated “Tier 1”, and are subject to more stringent regulations. While general criteria for the addition of BSAT to the SATL have been published, along with criteria for Tier 1 designation, there are no clearly defined, publicly available steps for de-tiering or de-listing BSAT, making it difficult to decipher paths to risk reduction. We set out to better understand how the government has historically chosen to list and tier BSAT, to create a generalized profile of Tier 1 and non-Tier 1 BSAT, and to design a methodology that the government can utilize in efforts of de-risking BSAT. To these ends, we conducted a literature review compiling key information on all BSAT, with a specific focus on development and availability of vaccines and therapeutics, as well as evidence and/or reports of prior weaponization efforts. We then performed statistical analyses to compare Tier 1 BSAT to non-Tier 1 BSAT, allowing us to develop a “prototype” that describes the characteristics that are typical of each. Finally, we used these results to design a set of “priority” experiments and threshold goals for perceived risk criteria, the results of which enable clearer avenues to de-risking, and potentially also de-tiering and de-listing, of BSAT. Our results represent a call to action to bolster biosecurity through the utilization of BSAT prototyping, key experiments, and threshold implementation, all in an effort to enable evidence-based risk reduction of select agents.